(untitled) (Editora Impacto Científico, 2025)
This study analyzed failures in the production and distribution of hospital diets, highlighting the relationship between low service quality and hospital malnutrition. Malnutrition, exacerbated by poor diet acceptance (Mendes et al., 2019; Fischer et al., 2021), is worsened by an institutional culture that undervalues sensory aspects in favor of technical control (Diez Garcia, 2006). The application of hospital gastronomy techniques was shown to significantly increase patient satisfaction and reduce the Rest-Intake Index (IR), proving to be an effective tool for increasing food intake (Santos et al., 2017). However, distribution failures, such as inadequate temperature and diet errors, persist as critical safety risks. Process standardization, rigorous quality management, and humanized care (Mendes et al., 2019) are essential to transform the oral diet into a safe and effective therapeutic strategy, fighting waste and malnutrition. DOI: https://doi.org/10.56238/edimpacto2025.090-031